(untitled) (Nigerian Journal of Technology, 2020)
This paper presents optimizing the control and automation of variable torque on 3-phase induction motor using programmable neuro logic controller (PNLC) and variable frequency drive (VFD). The system was designed by developing a transfer model of the nonlinear input current from the load cells and feed to an improved PLC model for an approximate current function which is identified by the VFD with respect to the controlled load torque to power the 4.07KW rated 3-phase induction motor. The models were implemented using control system toolbox, neural network toolbox and simulated with Simulink in MATLAB. From the simulation of the improved controller model, the step response time performance of the PLC was improved from 2.25s to 1.22s with the PNLC.The simulation result of the VFD controlled 3-PIM motor shows that 37.07% of energy (power) was conserved compared to a characterized system with 20% energy conservation rate. http://dx.doi.org/10.4314/njt.v39i3.30